Evaluation of the adverse effects of subcutaneous carprofen over six days in healthy cats - Steagall, P. V. M. [UNESP]; Moutinho, Flavio Quaresma [UNESP]; Mantovani, F. B. [UNESP]; Passarelli, D. [UNESP]; Thomassian, A. [UNESP] (Elsevier B.V., 2009)
This study evaluated the adverse effects of carprofen in seven healthy cats. Values for CBC, biochemical profiles and platelet aggregation were measured before and at seven days after SID treatment with subcutaneous carprofen: 4 mg/kg (day 1), 2 mg/kg (day 2 and 3) and 1 mg/kg (day 4 and 6) (CG) or 0.35 ml of saline (SG) for six days in a randomized, blinded, cross-over study with a four-week washout period. No treatment was given on day 5. Endoscopy of the GI tract was performed pre-treatment and on day 7 post-treatment. There were no significant changes in hematological profiles, biochemical profiles and endoscopy grading scores within nor between groups, except for lower albumin values at baseline than on day 7 (CG), and globulin and ALP values were higher at baseline than on day 7 in CG and SG. SC administration of carprofen over six days did not cause any adverse effects on gastrointestinal, hematological, or serum biochemical variables. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cat; Carprofen; NSAIDs; Adverse effects; Analgesia; Pain